2017
DOI: 10.3386/w23035
|View full text |Cite
|
Sign up to set email alerts
|

Do Anti-Poverty Programs Sway Voters? Experimental Evidence from Uganda

Abstract: A Ugandan government program allowed groups of young people to submit proposals to start skilled enterprises. Among 535 eligible proposals, the government randomly selected 265 to receive grants of nearly $400 per person. Blattman et al. (2014) showed that, after four years, the program raised employment by 17% and earnings 38%. This paper shows that, rather than rewarding the government in elections, beneficiaries increased opposition party membership, campaigning, and voting. Higher incomes are associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…4 Our study advances the literature by providing compelling evidence that reducing vulnerability decreases citizens' participation in clientelist exchanges. Second, our electoral findings may be interpreted as corroborating a related hypothesis of Blattman, Emeriau, and Fiala (2017): economic independence frees the poor to express support for opposition candidates. Third, by showing how these changes in the political equilibrium are concentrated among voters in ongoing relationships, our study complements research by Finan and Schechter (2012) and Calvo and Murillo (2013), which documents how vote buying and clientelism operate through established networks based on reciprocal, partisan, or personal ties.…”
Section: Introductionsupporting
confidence: 79%
“…4 Our study advances the literature by providing compelling evidence that reducing vulnerability decreases citizens' participation in clientelist exchanges. Second, our electoral findings may be interpreted as corroborating a related hypothesis of Blattman, Emeriau, and Fiala (2017): economic independence frees the poor to express support for opposition candidates. Third, by showing how these changes in the political equilibrium are concentrated among voters in ongoing relationships, our study complements research by Finan and Schechter (2012) and Calvo and Murillo (2013), which documents how vote buying and clientelism operate through established networks based on reciprocal, partisan, or personal ties.…”
Section: Introductionsupporting
confidence: 79%
“…However, the relationship between government spending programs and incumbent support are mixed. Some studies have shown that welfare programs increase voter turnout and support for incumbent politicians (Galiani et al, 2019; Manacorda et al, 2011; Zucco Jr, 2013), others have found null effects (Green, 2006; Imai et al, 2020), and even opposite results (Blattman et al, 2018). However, despite the importance of social welfare program in authoritarian countries to maintain regime legitimacy, few works examined the impacts of social policies on public opinion in authoritarian countries.…”
Section: Introductionmentioning
confidence: 99%